Signaling by the Fund : A Historical Review. (Policy Papers; Policy Paper, 2004)
The objective of this paper is to review the Fund's thinking about signaling since its inception, with a view to drawing lessons for the design of possible signaling mechanisms. Over the years, the Fund has both reflected on the ways in which its main activities - especially surveillance and use of Fund resources (UFR) - send signals, and has created instruments for the express purpose of signaling. Overall, attempts to 'design' signaling mechanisms have been less than fully successful. This paper attempts to elucidate why, drawing primarily on the Fund's own thinking and assessments.